Auto-ethnography - Sikes, Patricia J. (Los Angeles, Calif. SAGE Publications, 2013)
"From the 1980s onwards, there has been what has frequently been described as an auto/biographical turn in the social sciences and also in the arts and humanities. Changes in conceptions of self, society and identity, post-modern, post-structural and post-colonial influences and sensibilities to name but a few have all played their part in focusing attention on to, and valorising the perceptions and experiences of the individual...this new four-volume set seeks to capture the important articles that have come out of the field over the past decades. Framed by a newly-written introductory chapter, the collection includes work that spans disciplinary boundaries, bringing together a comprehensive resource"--Publisher.
Volume 1. Pt. 1. Origins, antecedents of autoethnographic research -- Pt. 2. Approaches to, and critiques of, autoethnographic research -- Volume 2. Pt. 2. (continued) Approaches to, and critiques of, autoethnographic research -- Volume 3. Pt. 3. Ethical concerns around autoethnography -- Pt. 4. Writing and re-presenting autoethnographic research -- Volume 4. Pt. 5. Speaking for myself.
Keywords: Ethnology -- Biographical methods; Ethnology -- Authorship